Gendered discourses of facilitation in a probation learning environment: challenging the heteronormative ideal. Issue 4 (3rd July 2016) - Perry, Emma
Abstract : This article focuses on the cognitive behavioural rehabilitation programmes run by the probation service in the UK. Drawing on Judith Butler's assertion that both sex and gender are discursively produced and Becky Francis' notion of gender monoglossia and heteroglossia, the article seeks to analyse and problematise the gendered discourses of facilitation that were mobilised by policy-makers and practitioners in this setting. The dominant institutional model of heteronormative facilitation promoted the ideal of each programme being delivered by one female and one male facilitator in order to provide a gender 'balance'. But underpinning this ideal lay the binarised and essentialist notion that 'masculinity' arose naturally from the male body and 'femininity' from the female body. Female facilitators were positioned as bringing a calming and non-threatening atmosphere to the group and as naturally possessing skills of 'empathy' and 'warmth'. Male facilitators were highly valued by managers, but were also under pressure to perform masculinity in very specific ways that were linked to notions of intellectual, rational, 'middle-class' masculinity. Through an analysis of interviews with probation practitioners and session observations, the article highlights that despite these dominant institutional constructions, a variety of complex and contradictory performances of 'masculinity' and 'femininity' were mobilised in this environment.